Un geste d’hospitalité aux demandeurs d’asile: Une analyse de la mobilisation du collectif Bridges not Borders - Belkhodja, Chedly; Gratton, Cassandre (Refuge: Canada's Journal on Refugees, 2022)
This article focuses on the mobilization of a collective created by citizens, Bridges not Borders (BnotB), that has been working to defend the asylum seekers that cross the Canada-U.S. border “irregularly” since 2017. The case of BnotB contributes to the literature on borders by bringing a perspective interested in the dynamics and mobilizations of citizens coming to the help of vulnerable persons across border crossings. Based on content analyses and semi-structured interviews, this case study allows us to present a “bottom up” form of action, led by citizens mobilized by migration issues, which we define under the gesture of hospitality.